Preludes [compact disc] - Chopin, Frédéric, 1810-1849 (Universal Music Classics, 2015)
Fifteen years after his historic first prize at the Chopin Competition in 2000, Yundi returns to the repertoire in which he first came to public and critical acclaim, and which has continued to inspire some of his most dazzling performances.